Teachers' Choices of Teaching Methods for Environmental Education: A case study of Life Skills teachers at a primary school in South Africa - Melishnee Ruthanam; Poovendhree Reddy; Daisy Pillay (Environmental Association of Southern Africa, 2021)
The success of environmental education has been attributed to several factors including teachers' competencies and attitudes, teaching methodologies, availability of resources, and curriculum design. Many researchers in environmental education suggest that innovative and resourceful teaching approaches may translate into meaningful environmental education. This study provides an insight into the influence of this on environmental education in a South African classroom through a qualitative approach. Interviews were conducted to understand the teaching approaches used in the subject of Life Skills. The findings of the study suggest that the pedagogical content knowledge and identity of the teacher are determining factors for teachers' pedagogical choices. This paper suggests that it is not the resources that are crucial to learning, rather the presence of a resourceful teacher. A resourceful teacher is able to introduce innovation regardless of the availability of teaching resources. This information could inform pre-service teacher training programmes in focusing on the development of a resourceful environmental education teacher.